2011
DOI: 10.1007/s11418-011-0554-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclooxygenase-2 and inducible nitric oxide synthase by silymarin in proliferating mesenchymal stem cells: comparison with glutathione modifiers

Abstract: Silymarin, a mixture of flavonolignans, is extracted from milk thistle (Silybum marianum) and has a strong antioxidant activity and exhibits anticarcinogenic, anti-inflammatory, and cytoprotective effects. In this study we attempted to determine whether silymarin and the glutathione modifiers, buthionine sulfoxamine (BSO) and N-acetylcysteine (NAC), are involved in regulation of cyclooxygenase (COX)-2 and inducible nitric oxide synthase (iNOS) in proliferating mesenchymal stem cells (MSCs). Cellular glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Silymarin can grow there easily to use in skin protecting products. The photo aging and reduce wrinkles, dryness; it can also stimulate the proliferation of human keratinocytes, induce skin moisture [33][34][35]. Silymarin has a protective effect on cells against H2O2 as an antiaging effect [48] and increases total antioxidant capacity of cell extract [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silymarin can grow there easily to use in skin protecting products. The photo aging and reduce wrinkles, dryness; it can also stimulate the proliferation of human keratinocytes, induce skin moisture [33][34][35]. Silymarin has a protective effect on cells against H2O2 as an antiaging effect [48] and increases total antioxidant capacity of cell extract [49].…”
Section: Discussionmentioning
confidence: 99%
“…Silymarin is a safe plant for treatment of diseases that isn't toxic even at higher physiological doses [32]. It also decreases the level of COX-2 that relates to carcinogenesis [33]. minimum effective dose of this plant can be used for maximum protective effect [34].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is explained by the ability of SIL to inhibit expression of NOS and cause elevation of GSH level. 26 Of interest, CAN administration corrected the levels of serum aminotransferases (ALT & AST) and GGT as compared to that of fibrotic rats. Simultaneously, CAN attenuated the hepatic fibrosis in treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cardiovascular mortality of aging can also be explained by vascular inflammation and oxidative stress (Gencel et al ., ). Cyclooxygenase‐2 and the inducible form of NOS are inducible in inflammation, modulated by SM in proliferating mesenchymal stem cells (Ahmadi‐Ashtiani et al ., ) and by silibinin in tumorigenic mouse lung epithelial cells together with proinflammatory cytokine tumor necrosis factor‐α (Tyagi et al ., ). These authors demonstrated that anti‐inflammatory activity of silibinin is the result of a possible inhibition of the signal transducers and activators (STATs) and nuclear factor‐κB inflammatory pathways in the cells.…”
Section: Discussionmentioning
confidence: 99%